Influence of Temperature and Duration of the Process on the Degree of Nickel Extraction - Bekhzod Farmanov Ilkhomovich; Tavashov Shakhzod Khujaxmatovich (International Journal on Orange Technologies, 2022)
To date, in the global industry, special attention is paid to the synthesis of high-strength, with low hydraulic resistance, improved geometric and increased specific surface area of catalyst granules. In this aspect, an important task is to develop a technology for the production of our own highly efficient and durable catalysts based on the processing of spent industrial catalysts. To do this, it is necessary to substantiate a number of scientific solutions, including in the following areas: development of nickel extraction technology from spent industrial catalysts of the GIAP-8 series, technology for obtaining high-strength aluminum oxide carriers and scientific bases for obtaining a nickel-containing catalyst on an aluminum oxide carrier.